ARTEMIN Promotes Oncogenicity and Resistance to 5-Fluorouracil in Colorectal Carcinoma by p44/42 MAPK Dependent Expression of CDH2 - Zhuang, Qiu-Shi; Sun, Xin-Bao; Chong, Qing-Yun; Banerjee, Arindam; Zhang, Min; Wu, Zheng-Sheng; Zhu, Tao; Pandey, Vijay; Lobie, Peter E. (Frontiers in Oncology, 2021)
ARTEMIN (ARTN), one of the glial-cell derived neurotrophic factor family of ligands, has been reported to be associated with a number of human malignancies. In this study, the enhanced expression of ARTN in colorectal carcinoma (CRC) is observed; the expression of ARTN positively correlates with lymph node metastases and advanced tumor stages and predicts poor prognosis. Forced expression of ARTN in CRC cells enhances oncogenic behavior, mesenchymal phenotype, stem cell-like properties and tumor growth and metastasis in a xenograft model. These functions are conversely inhibited by depletion of endogenous ARTN. Forced expression of ARTN reduces the sensitivity of CRC cells to 5-FU treatment; and 5-FU resistant CRC cells harbor enhanced expression of ARTN. The oncogenic functions of ARTN are demonstrated to be mediated by p44/42 MAP kinase dependent expression of CDH2. Inhibition of p44/42 MAP kinase activity or siRNA mediated depletion of endogenous CDH2 reduces the enhanced oncogenicity and chemoresistance consequent to forced expression of ARTN induced cell functions; and forced expression of CDH2 rescues the reduced mesenchymal properties and resistance to 5-FU after ARTN depletion. In conclusion, ARTN may be of prognostic and theranostic utility in CRC.